2022
DOI: 10.1038/s41467-022-29967-1
|View full text |Cite
|
Sign up to set email alerts
|

Periodic formation of epithelial somites from human pluripotent stem cells

Abstract: During embryonic development, epithelial cell blocks called somites are periodically formed according to the segmentation clock, becoming the foundation for the segmental pattern of the vertebral column. The process of somitogenesis has recently been recapitulated with murine and human pluripotent stem cells. However, an in vitro model for human somitogenesis coupled with the segmentation clock and epithelialization is still missing. Here, we report the generation of human somitoids, organoids that periodicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 80 publications
(130 reference statements)
1
50
0
Order By: Relevance
“…Next, we used the monkey reference to evaluate several human stem cell embryo models. By performing integrated analyses, we found that the main cell types from several gastruloids 42,43 , heart-forming organoids (HFOs) 44,45 , neuruloids (for example, the MiSTR patterned neural tube that mimics the A-P axis 46 and the two-dimensional micropatterned, light-induced or chip-based neural tube that mimics the D-V axis [47][48][49] ) and somitoids 50 generally overlapped with the CS8-11 monkey embryos reference (Extended Data Figs. 8g,h, 9 and 10 and Supplementary Tables 12 and 13), although notable differences were observed.…”
Section: Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Next, we used the monkey reference to evaluate several human stem cell embryo models. By performing integrated analyses, we found that the main cell types from several gastruloids 42,43 , heart-forming organoids (HFOs) 44,45 , neuruloids (for example, the MiSTR patterned neural tube that mimics the A-P axis 46 and the two-dimensional micropatterned, light-induced or chip-based neural tube that mimics the D-V axis [47][48][49] ) and somitoids 50 generally overlapped with the CS8-11 monkey embryos reference (Extended Data Figs. 8g,h, 9 and 10 and Supplementary Tables 12 and 13), although notable differences were observed.…”
Section: Articlementioning
confidence: 99%
“…To do integration analysis for monkey and human single-cell data, the human CS7 embryo 2 and various embryoid datasets including gastruloids 42,43 , HFOs 45 , neuruloids [46][47][48][49] and somitoids 50 were prepared (Extended Data Figs. 8a-d,g, 9a,b and 10a,d,g).…”
Section: Comparison Of Single-cell Transcriptomic Dataset Among Mouse...mentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of endogenous and exogenous ECM sources on epithelial morphogenesis has been addressed in other in vitro systems. An example are experimental paradigms that show the formation of somites, for which either a low concentration of Matrigel in the culture medium ( Sanaki-Matsumiya et al ., 2022; van den Brink et al ., 2020; Veenvliet et al ., 2020) or differentiation of ECM-producing cells within the tissue are required ( Amadei et al ., 2022; Bao et al ., 2022; Lau et al ., 2022). Similarly, breast luminal epithelial cells can be polarized in vitro by exogenous addition of laminin-1, or co-culture with ECM-producing myoepithelial cells ( Gudjonsson et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Given their accessibility and scalability, in vitro models of embryogenesis offer the potential for high-throughput readouts of broad chemical screens, offering an exciting toolkit to accelerate our understanding of epigenetic regulator function in the establishment of cell identities. Finally, the recent implementation of human in vitro models of embryogenesis faithfully recapitulating critical stages of pre- [80,81] and postimplantation [82][83][84] development may help overcome ethical limitations associated with human embryo research and offer a unique path to understand how conserved epigenetic principles are across mammals as well as to more directly address aspects of these findings as they relate to reproductive and fetal health.…”
Section: Discussionmentioning
confidence: 99%